Thermal energy storage with phase change materials to increase the efficiency of solar photovoltaic modules. (October 2017) - Klemm, Torsten; Hassabou, Abdelhakim; Abdallah, Amir; Andersen, Olaf
Abstract: Thermal management is an essential design part for the application of solar photovoltaic (PV) modules, especially in hot regions in the Middle East. The operating temperature influences the efficiency as well as the reliability and lifespan of the modules. The purpose of this paper is to evaluate a new concept of passive thermal management by combining a phase change material (PCM) with metallic fibre structures in a PCM module to enable customised heat transfer properties. The module is mounted on the backside of the solar module. The system is assessed by numerical calculations, performed with the commercial finite-element software COMSOL Multiphysics. The results show that, compared to the case without PCM module, the peak temperature of the solar module for a daily cycle can be decreased by approximately 20 K by an adequate design with a limited usage of metallic structure. A parameter variation with different fibre structure properties, PCM, PCM module sizes and contact resistances was conducted and show the limits and main influence parameter on the system performance.